2019
DOI: 10.1002/cre2.193
|View full text |Cite
|
Sign up to set email alerts
|

Association between p62 expression and clinicopathological characteristics in oral leukoplakia

Abstract: Objective Oral leukoplakia is keratinized lesions in the buccal mucosa, tongue, and gingiva. It is the most common oral precancerous lesion; oxidative stresses and irrelevant autophagy have been reported to be the cause of oncogenesis. p62, a cytoplasmic protein induced by oxidative stress, is an adaptor protein involved in the formation of protein aggregates and induction and inhibition of autophagy. The inhibition of autophagy induces p62 overexpression and promotes oncogenesis via the oncogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
0
4
0
2
Order By: Relevance
“…Staining for p62 was evaluated separately for nucleus, cytoplasm, and aggregation. In accordance with our previous research, we defined a cell positive for p62 aggregation staining as one with at least one dot of accumulation in the cytoplasm in 20× and 40× field of view [ 18 ]. Representative images of p62 aggregation are shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Staining for p62 was evaluated separately for nucleus, cytoplasm, and aggregation. In accordance with our previous research, we defined a cell positive for p62 aggregation staining as one with at least one dot of accumulation in the cytoplasm in 20× and 40× field of view [ 18 ]. Representative images of p62 aggregation are shown in Figure 2 .…”
Section: Methodsmentioning
confidence: 99%
“…We previously reported that the expression of autophagy-related markers, including p62, at the resection margins of OSCC was associated with tumor recurrence [ 17 ]. We also found that p62 expression in the nucleus and p62 aggregation in oral leukoplakia were related to the presence or absence of epithelial dysplasia [ 18 ]. This suggests that p62, an adaptor of selective autophagy, may be useful as a marker for assessing the risk of recurrence at the resection margin of OSCC as well as the risk of malignant transformation in precancerous lesions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La expresión de 8-hidroxi 2'-desoxiguanosina en el cáncer Tequio 5 (15), 2022: [31][32][33][34][35][36][37][38][39][40] ISSN: 2594-0546 TEQUIO, mayo-agosto 2022, vol. 5, no.…”
Section: -Hydroxy 2'-deoxyguanosine Expression In Cancerunclassified
“…En adición a lo anterior, ahora se sabe que los niveles salivales del 8-OHdG están aumentados en los pacientes con cáncer oral de células escamosas y otros desórdenes orales potencialmente malignos (Bahar, Feinmesser, Shpitzer, Popovtzer y Nagler, 2007); (Nandakumar, Nataraj, James, Krishnan y Mahesh, 2020).Por el contrario, en las lesiones precancerosas de pacientes con leucoplasia oral, la expresión del 8-OHdG se mantiene sin cambios(Yoshida et al, 2019), lo cual sugiere que la sobreexpresión de esta molécula pudiera estar restringida únicamente a las células cancerígenas de la cavidad oral. No obstante, también se ha informado que la expresión del 8-OHdG en pacientes con carcinoma de células escamosas no incrementa (Yoshifuku, A., Fujii, K., & Kanekura, T. 2018), lo cual está en contraposición a lo descrito líneas arriba en este párrafo.Con relación a otros tipos de cáncer, se tiene la evidencia de que la expresión del 8-OHdG aumenta en pacientes con adenocarcinoma de esófago y hepatocarcinogénesis(Chuma et al, 2008); (Räsänen, Sihvo, Ahotupa, Färkkilä y Salo, 2007).…”
unclassified